Incentives, Resources and Combinations of Innovation Radicalness and Innovation Speed. (21st December 2017) - Behrens, Judith; Patzelt, Holger
Abstract: Although scholars have independently explored the antecedents of innovation radicalness and innovation speed, this study's focus on combinations of radicalness and speed offers a number of new insights. Drawing on a comparative case study approach of ten innovation departments of large organizations, the authors' findings provide evidence that intrinsic rewards trigger innovation radicalness, but the simultaneous presence of extrinsic rewards diminishes innovation speed. Further, the authors show that the availability of high levels of non‐financial resources increases innovation radicalness, but the additional provision of high levels of financial resources leads to a slower process of developing these radical innovations to market. The analysis also uncovers the mechanisms by which extrinsic rewards and financial resources slow down the development of radical innovations. The authors discuss the implications of these findings for the literature on innovation management and managerial practice.